The best of both worlds? combining specialist practice with hospital consultancy. (2nd April 2019) - Scott, Paul; Shelton, Andrew T
Abstract : This article describes the experience of undertaking post specialty consultant training, on a part-time basis, with its advantages and disadvantages, and how this experience is transferred into a current practice combining a hospital consultant and specialist practice position, with its challenges and benefits. CPD/Clinical Relevance: The workforce providing primary and secondary care orthodontics is evolving and it is important that alternative training modalities and working practices are available to allow flexibility in provision of care.